Combination of photos, definitions, and fill-in-the-blank tasks in Quizlet: a concern about learning academic vocabulary in online listening classes - Tien Thinh Vu; Diem Bich Huyen Bui (Journal on English as a Foreign Language, 2023)
The role of vocabulary has been proven to be crucial in learning both receptive and productive skills. However, in terms of listening skills, students may face enormous challenges in comprehending the content of a listening passage and, therefore, fail to take notes. This study aimed to investigate the impact of using Quizlet more creatively in the vocabulary section of online academic listening classes. Participants were 62 intermediate-level students from two online academic listening classes, divided into a control and an experimental group. While students in the control group did the tasks in their books or handouts from the teacher, those in the experimental group used Quizlet for eight weeks. A mixed method with t-tests and questionnaires was applied in this research. Results from t-tests revealed that students in the experimental group had better performance in remembering the definition of vocabulary they had learned and using correct vocabulary to fill in the blanks in sentences. Findings in questionnaires supported the improvement in the post-test that the students in the experimental group showed a high level of concentration, engagement, and excitement in class. The study's outcome sheds light on further research on using Quizlet in EFL classrooms.